Identities on Changhee Polynomials Arising from λ-Sheffer Sequences - Byung Moon Kim; Taekyun Kim; Jin-Woo Park; Taha Ali Radwan (Complexity)
In this paper, authors found a new and interesting identity between Changhee polynomials and some degenerate polynomials such as degenerate Bernoulli polynomials of the first and second kind, degenerate Euler polynomials, degenerate Daehee polynomials, degenerate Bell polynomials, degenerate Lah–Bell polynomials, and degenerate Frobenius–Euler polynomials and Mittag–Leffer polynomials by using λ-Sheffer sequences and λ-differential operators to find the coefficient polynomial when expressing the n-th Changhee polynomials as a linear combination of those degenerate polynomials. In addition, authors derive the inversion formulas of these identities.